Strategi Pemasaran Bank Rakyat Indonesia Tbk (BRI) Dan Adopsi Technology Acceptance Model Pada Program Bri Mobile - Ilham Putra Wendi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
PT Bank Rakyat Indonesia (Persero) Tbk, or BRI, is one of the largest banks in Indonesia which has played an important role in supporting economic growth and social welfare for more than a century. BRI Mobile is a banking technology innovation developed by BRI to meet the digital banking needs of its customers. BRI Mobile allows customers to access banking services, transfer funds, pay bills and carry out various other financial transactions via their mobile devices. With the BRI Mobile application, BRI has succeeded in bringing the ease and convenience of banking into the hands of its customers, facilitating access to more efficient and practical financial services. The research results show that the adoption of TAM in this program can make a significant contribution to the company's marketing strategy.